(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Understanding consumers’ behavior is an important factor for the expansion of a business. A better understanding of the factors that influence consumption behavior of consumer can help marketers to undertake better marketing strategies and predict how consumers would respond to those marketing strategies. This study was undertaken to examine urban consumer behavior towards fluid milk consumption in Mymensingh city using primary data of 60 respondents through purposive sampling method. Three types of milk were considered from branded fluid milk such as UHT, chocolate and pasteurized fluid milk, and raw fluid milk as unbranded milk. The results revealed that about 33 percent of the respondents consumed branded milk, 36 percent consumed unbranded milk and 30 percent consumed both branded and unbranded milk. The results of the logit model indicated that probability of purchasing branded milk were positively related to awareness of advertisement, expenditure on fluid milk and quality of branded fluid milk, whereas, negatively related to agricultural occupation and accessibility to cow milk. In regards of attitude, most of the consumer responded that they did not think about the brand name in the time of emergency. Availability of branded fluid milk was important for them. Advertisements were found to have great impact on the consumer to choose branded fluid milk. Marketers need to take into account the choice, taste, attitude of the consumers properly in order to make their business successful. J Bangladesh Agril Univ 18(2): 479–485, 2020 https://doi.org/10.5455/JBAU.96071